NUEVOS EOTOMARIIDAE (GASTROPODA) DEL PALEOZOICO SUPERIOR DE ARGENTINA (Ameghiniana, 2013)
A new gastropod genus (Barrealispira) is proposed herein to include Upper Paleozoic specimens from the Uspallata-Iglesia basin. Two species of gastropods, Barrealispira mesigosi sp. nov. and Mourlonia striata (Sowerby), from the Hoyada verde Formation (Levipustula Zone) are described and figured. Paleoenvironmental meaning of some features associated to the fossiliferous level are analyzed.